Neuroligin-1 knockdown reduces survival of adult-generated newborn hippocampal neurons - Schnell, Eric; Long, Thomas H.; Bensen, AeSoon L.; Washburn, Eric K.; Westbrook, Gary L. (Frontiers in Neuroscience, 2014)
Survival of adult-born hippocampal granule cells is modulated by neural activity, and thought to be enhanced by excitatory synaptic signaling. Here, we report that a reduction in the synaptogenic protein neuroligin-1 in adult-born neurons in vivo decreased their survival, but surprisingly, this effect was independent of changes in excitatory synaptic function. Instead, the decreased survival was associated with unexpected changes in dendrite and spine morphology during granule cell maturation, suggesting a link between cell growth and survival.